2022
DOI: 10.1002/hsr2.741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of standardized root extract of ashwagandha (Withania somnifera) on well‐being and sexual performance in adult males: A randomized controlled trial

Abstract: Background and Aim: In Ayurveda, ashwagandha is a popular plant for promoting youthful energy, longevity, and overall well-being. It is also an excellent aphrodisiac herb that aids in the improvement and maintenance of normal sexual health. The present study aims to evaluate the effect of ashwagandha root extract on improving sexual health in adult males.Methods: In this 8-week randomized, double-blind, placebo-controlled study, we investigated the aphrodisiac property of an ashwagandha root extract in adult m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The oral Administration of ARE has been previously reported to promote an increase in male testosterone among human participants (ref. 35), although the mechanisms still need to be explored, and the results of this study provide additional evidence that ARE may be administered for therapeutic purposes without inducing deleterious effects on the fertility and reproductive health of males. We also observed improvements in serum testosterone (p=0.012), DHT, Prolactin, FSH, and LH levels.…”
Section: )mentioning
confidence: 86%
“…The oral Administration of ARE has been previously reported to promote an increase in male testosterone among human participants (ref. 35), although the mechanisms still need to be explored, and the results of this study provide additional evidence that ARE may be administered for therapeutic purposes without inducing deleterious effects on the fertility and reproductive health of males. We also observed improvements in serum testosterone (p=0.012), DHT, Prolactin, FSH, and LH levels.…”
Section: )mentioning
confidence: 86%
“…When compared to a placebo, ashwagandha root extract consumption was related to a statistically significant rise in total DISFM scores. It was also linked to a statistically significant increase in serum testosterone levels [106].…”
Section: Treatment Based On Plants and Other Natural Productsmentioning
confidence: 95%
“…Like any botanical drugs and pharmaceutical drugs, there have been some adverse effects reported after w. Somnifera consumption. In a clinical trial, seven adult males reported feeling sleepiness, mild abdominal and joint pain after consuming ashwagandha capsule (Chauhan et al, 2022). Withania somnifera is still not approved by the U.S. Food and Drug Administration (FDA) and has not been used legally to treat diseases on large scale.…”
Section: Role Of W Somnifera In Covid-19 Infectionmentioning
confidence: 99%